Problems Perceived by the Women Workers under MGNREGA in Jaipur District of Rajasthan (Indian Journal of Extension Education, 2017)
The present study was conducted in Jaipur District of Rajasthan, to find out the problems perceived by women workers in MGNREGAin 2016. For this, 120 MNREGAwomen workers were selected and information was collected with the help of structured interview schedule and data were analysed with the appropriate statistical tools. The major problems perceived by the women workers were lack of time to care the children in the home, undue delay in getting the job card and poor access to drinking water at work site.